Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Kantor Kecamatan - Nabila , Ayu Arisanti; Gentawicara, Dinda (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This research will be conducted at the Pangkalan Kerinci Sub-District Office, Pelalawan Regency and the observation time is in early September 2024. The purpose of this study is to determine the effect of service quality on public satisfaction at the Pangkalan Kerinci Sub-District Office, Pelalawan Regency. The sample in this study was 95 people who had been simplified using the Slovin formula. In this study, the sample method used the accidental sampling technique. Data analysis in this study used descriptive and quantitative methods. Based on the results of the research analysis, it was found that Service Quality had a significant effect on public satisfaction at the Pangkalan Kerinci Sub-District Office, Pelalawan Regency where t count = 13.179> t table = 1.98552. The results of simple linear regression obtained the regression equation Y = 4.200 + 0.772X, this means that the results of the study are the same as the research hypothesis. The R2 value is 0.814, which means that the influence of Service Quality has a significant effect on public satisfaction at the Pangkalan Kerinci District Office, Pelalawan Regency, is 66,1% while 33.9% is influenced by other variables not studied in this study.